(6x+11+9x)=

Simple and best practice solution for (6x+11+9x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+11+9x)= equation:


Simplifying
(6x + 11 + 9x) = 0

Reorder the terms:
(11 + 6x + 9x) = 0

Combine like terms: 6x + 9x = 15x
(11 + 15x) = 0

Remove parenthesis around (11 + 15x)
11 + 15x = 0

Solving
11 + 15x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 15x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 15x = 0 + -11
15x = 0 + -11

Combine like terms: 0 + -11 = -11
15x = -11

Divide each side by '15'.
x = -0.7333333333

Simplifying
x = -0.7333333333

See similar equations:

| r+7-1=6 | | 0.7=x-1.2x | | b/5-9=-1 | | 9000=.07*1*x | | 43=-7+5x | | 3ln(3x-4x^3)=0 | | X+2y=195 | | x*y=24 | | 2.8=ln(y) | | 9000=.05*1*x | | 6x-6x+9=9 | | 15=1+6a+a | | 15x+5=135 | | 1+5p+8p=1 | | x+y=39 | | 6r-5r=-7 | | 1x+2y=49 | | -9=c/12 | | 98=6+34 | | 5=7v+8+4 | | Ln(8x+2)=Ln(4x-10) | | 50/5= | | 12x+5x+7=9 | | -6=k-8-1 | | 4(3-5x)=3(-3x+15) | | 4/x=2/11 | | 10x-3=7x-11 | | 10/2= | | 13=-7p-6p | | a^2-9=40 | | x/5=6/2 | | 5x+11=3+8x-7 |

Equations solver categories